Incorporating Digital Technology for Preparing English Teaching Materials in the Merdeka Curriculum by PPG Graduates: A Case Study at a Public University - Della Wilza Noviska; Aniza Rilda; Ulmala Sari; Ahmad Syauqi Harsyah (Institut Agama Islam Negeri Palopo, 2025)
This study is aimed to investigate the challenges that teachers encounter when integrating technology into the preparation of teaching materials and how PPG graduates perceive the impact of technology on the efficiency and effectiveness of preparing teaching materials. The research methodology involves qualitative techniques, including interviews with PPG graduates, to gather data and analyze their perceptions. The study found that there are several challenges faced by the participants when they utilize technology in preparing their teaching material. The challenges encompassed internal and external factors. Simultaneously, it emphasizes the positive impacts of integrating technology in enhancing learning experiences considering both its benefits and challenges. The article provides a comprehensive exploration of the intricate relationship between education, technology, and teacher readiness in Indonesia.